Shallow-water sea fans: the exceptional assemblage of Leptogorgia sarmentosa (Anthozoa: Gorgoniidae) in the Genoa harbour (Ligurian Sea). Issue 1 (1st January 2018) - Betti, F.; Bo, M.; Bava, S.; Faimali, M.; Bavestrello, G.
Abstract: An exceptional assemblage of the sea fan Leptogorgia sarmentosa (Anthozoa: Gorgoniidae) was observed inside the Genoa harbour, which represents one of the major Mediterranean ports. The studied assemblage is confined in a shaded portion of a floating dock thriving in extremely shallow water, with specimens even touching the sea surface. It represents the shallowest population of this species and of this genus known worldwide. A total of 188 specimens were observed and measured: the maximum density of 45 specimens m −2 was reached in the most shaded part of the dock, where the maximum height of colonies (30 cm) was also recorded. Light measurements showed that the illuminance along the dock was comparable to that observed outside the harbour at 20 m depth, where the nearest colonies of L. sarmentosa were recorded for this region. This suggests that high levels of incident light might be putatively interpreted as the limiting factor in the upper bathymetrical distribution of the species. Despite the extremely shallow distribution, however, the population cannot be defined as intertidal as the floating dock avoids exposing the gorgonians to air. The chance to grow far from the silted bottom, but still in a turbid, sciaphilous and nutrient-enriched environment, probably enhanced the settling and growth of the colonies and allowed the formation of a dense and healthy population.